The fighter Mohamed Cherif Sahli and his contributions to writing Algerian national history - .khelifi, abdelkader (Journal of Social Sciences and Humanities, 2022)
This modest scientific paper aims to examine some of the contributions of the thinker and militant Mohamed Cherif Sahli (1906-1989), who represented a model for the generation of the Algerian national elite, which received a cultural and scientific formation in the wheels of the Francophone school, but remained true to his affiliation and identity as a political struggle and intellectual production, He showed a high spirit of struggle within the framework of his activities within the People's Party / Movement for the victory of democratic freedoms, and then in the arena of the liberation revolution 1954-1962 , when he was assigned media and diplomatic tasks related to communicating the voice of the revolution to French public opinion and representing it in the countries of the North Europe, which are the tasks that he managed efficiently and competently, and after independence he continued to serve the country for decades in the field of diplomatic work, as he left his mark clearly in this regard, and also made a distinguished contribution to enriching the National Library with very important works that came at a critical juncture in our journey. Historicism spoiled a great void at the time, in terms of the nature of the issues addressed, and the methodology of the presentation, so he was right, and he was the owner of the idea of the Copernican revolution to displace colonial universals in the field of history in Algeria, the strong voice that Early AR after defeating the colonizer, in favor of liberating history after the restoration of geography.